RESEARCH ON MICROPROPAGATION OF GREEN ROSE (Rosa L.) - Thi Thu Huong, Bui; Mai Thom, Nguyen; Huy Gioi, Dong (Journal of Forestry Science and Technology, 2021)
Green rose (Rose L.) is a beautiful, precious flower that is loved by many people all over the world. However, the source of seedlings of the ornamental flower variety is very limited. This study was conducted to rapidly propagate green roses by tissue culture. A solution of 0.1% HgCl2 was used to sterilize the samples; some plant growth regulators such as BA, Kinetin, and nanosilver were used to improve the efficiency of in vitro propagation. The results showed that (i) the using the solution HgCl₂ 0.1% for sterilizing the shoots in 10 minutes gave a high rate of clean, survival samples, nearly 69%; (ii) the MS medium supplemented with 30 g/L sucrose, 8 g agar, 1.5 mg/L BAP, and 6 ppm nanosilver was the best for shoot regeneration with regeneration rate was 95.56%, and average shoot height was approximately 3 cm after 2 weeks of culturing, (iii) the most suitable medium for shoot multiplication was the MS medium supplemented with 30 g/L of sucrose, 8 g/L agar, 1.5 mg/L BAP, and 0.25 mg/L Kinetin with a coefficient of 2.65, and the average shoot height was 2.25 cm, (iv) the shoots can have the best induction of rooting as culturing in the MS medium added 2 mg/L α-NAA, and 2 ppm nanosilver with the rooting rate was 76.67%, and average root length was around 3.3 cm after 4 weeks culturing.